Improving Teacher Work Motivation Through Academic Supervision In SDN Sendangmulyo 04 Semarang City - Rosamaji, Rosamaji (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2023)
This study is motivated by the low motivation of SDN Sendangmulyo 04 Semarang City teachers. The research aims to improve teachers’ work motivation through the results of academic supervision. One of the principal’s main tasks is as a supervisor. Therefore, supervision results can be used to improve teachers’ work motivation. Measurement is done through (1) attendance 15 minutes before the bell rings, (2) assessment in the learning process, (3) completeness of teacher administration, and (4) activeness in school activities. This research used a school action research method consisting of 2 cycles. The results of this study compare cycle I and cycle II and the teacher performance questionnaire. Based on the value of the results from cycle I showed that there were 20 teachers present 15 minutes before the bell rang, there were 12 teachers (41.38%), 14 teachers in the PBM process were still low (58.28%), there were 15 teachers had complete administration (51.72%), and there were still 17 teachers who were active in school activities (58.63%). In cycle II, 24 teachers where present 15 minutes before the bell rang (82.76%), 26 learning supervision scores increased (89.66%), 22 teachers had complete administration (75.87%), and 20 teachers were active in school activities (68.97%). After comparing the results from cycle, I and cycle II, there was an increase in teacher motivation in their performance. Academic supervision can increase teachers’ work motivation. The implications of increasing teacher motivation can improve student learning outcomes.